1997
DOI: 10.1016/s0014-5793(97)01151-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA synthesis and tube morphogenesis of cultured vascular endothelial cells by chondromodulin‐I

Abstract: Cartilage is an avascular tissue, and exhibits antiangiogenic properties. Cartilage extracts have been shown to contain an inhibitor for DNA synthesis in vascular endothelial cells in vitro. Here we purified the inhibitory activity in the 10-50 kDa fraction of guanidine extracts from fetal bovine epiphyseal cartilage, and found that the inhibitor was identical with chondromodulin-I (ChM-I). Purified ChM-I inhibited tube morphogenesis of cultured vascular endothelial cells, as well as DNA synthesis. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…The expression of chondromodulin‐1 is markedly decreased in BAV compared to TAV 35. Chondromodulin‐1, expressed in the aortic valve during development, inhibits cell proliferation and angiogenesis 36. Mice deficient for chondromodulin‐1 have thickened aortic valves with new blood vessels, which is one feature also observed in human mineralised aortic valves 35.…”
Section: Pathobiologymentioning
confidence: 99%
“…The expression of chondromodulin‐1 is markedly decreased in BAV compared to TAV 35. Chondromodulin‐1, expressed in the aortic valve during development, inhibits cell proliferation and angiogenesis 36. Mice deficient for chondromodulin‐1 have thickened aortic valves with new blood vessels, which is one feature also observed in human mineralised aortic valves 35.…”
Section: Pathobiologymentioning
confidence: 99%
“…1 This avascularity is abrogated in several valvular heart diseases (VHDs). [2][3][4] Chondromodulin-I, which is an antiangiogenic factor isolated from bovine cartilage, [5][6][7][8] is also expressed in the eye and is critically involved in the maintenance. Recently, we have reported that chondromodulin-I was abundantly expressed by the valvular interstitial cells in normal cardiac valves.…”
mentioning
confidence: 99%
“…Whereas chondrocytes of the avascular cartilage produce inhibitors of angiogenesis, hypertrophic chondrocytes produce angiogenic stimulators that initiate vascularization. The expression pattern of chm-I during development and in vitro and in vivo experiments with mature chm-I suggested an important role for chm-I in the proliferation and differentiation of chondrocytes, as well as in the vascular invasion of growth plates (15,16,18). Recent studies of chm-I expression in rats provided further evidence for a regulatory role of chm-I during vasculogenesis in the retina and the vitreous body (12).…”
Section: Discussionmentioning
confidence: 99%
“…Direct involvement of chm-I in angiogenesis was shown in vitro when recombinant mature chm-I inhibited proliferation and tube morphogenesis of endothelial cells in cell culture experiments (18). Injection of mature chm-I into growing mouse osteoblastomas inhibited angiogenesis and resulted in profound inhibition of tumor growth in vivo (15).…”
mentioning
confidence: 99%